Design and detailing of a scale-model two-storey RC frame for shaking table testing - Lejano, Emmanuel G.; Hernandez, Jaime Y. Jr.; Peralta, Mathew Harvey T. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
There are several studies regarding scale-model testing that has now become a vast project of many researchers. In other countries such as Korea, structural testing and analysis are investigated through physical models. The main purpose of this study is to determine the behavior of the scale-model structure subjected to certain seismic loading. In this study, an experimental 0.7 scale-model two-storey reinforced concrete frame tested on shaking table is used and treated as the prototype and the full-scale structure. The experimental structure is modeled and simulated using a structural analysis software to produce time history results and compared it to the experimental time history results for verification. Also, an analytical scale-model is developed and simulated using appropriate similitude law using the same software to verify the results. However, due to the fact that structure modelling means simplification of the real structure, yielding exact same results is not nearly possible due to its limitations. Hence, given that eliminating the errors is impossible, minimizing errors through variations in modelling such as re-modelling the structure is done repeatedly. The model that yielded the nearest exact same results is selected as the structure for scale-modelling. The structural plan ofthe scale-model structure based on the verified results of the analytical modelling is detailed as the final output of this study.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Earthquake simulators; Structural frames -- Models